Effects of Giving Kaffir Kaffir Extract ( Citrus hystrix ) on Blood Glucose Levels in Wistar Rats - Ika Dyah Kurniati; Dyah Mustika Nugraheni; Mutiara Aura Kusuma (Ahmad Dahlan Medical Journal, 2022)
Dyslipidemia is associated with cardiovascular disease as well as hyperglycemia and insulin resistance. One of the natural ingredients for controlling dyslipidemia is kaffir lime peel ( Citrus hystrix ), which contains flavonoids and polyphenols that act as antioxidants and regulate blood glucose. This study aims to prove the effect of kaffir lime peel in lowering blood glucose levels. Methods : Post-test only controlled group design study , using 25 wistar rats divided into 5 groups, namely group (K-) without high-fat diet and extract (K+) was given a high-fat diet alone, (P1) was given kaffir lime peel extract at a dose of 35 mg/kg BW rats/day, (P2) was given extract at a dose of 70 mg/kg BW rats/day and (P3) was given extract at a dose of 140 mg. /kgBW rats/day. The intervention was given for 3 weeks and then blood glucose levels were measured using the GOD-PAP method. The data were analyzed using the Kruskal Wallis test and continued with the Mann-Whitney test. Results : The results showed a significant difference in the mean GDS levels between groups p=0.011 (p<0.05), Mann-Whitney test showed K(-) against P1 (ρ=0.009), K(-) against P2 (ρ=0.016) , K(-) to P3 (ρ=0.028), and P1 to P2 (ρ=0.028).